EVALUATION OF CUO OXIDATION PARAMETERS FOR DETERMINING THE SOURCE AND STAGE OF LIGNIN DEGRADATION IN SOIL - Otto A.; Simpson M.J. (My University, 2006)
The composition of phenols and other aromatic compounds in organic and mineral soil horizons and their respective source vegetation from different climatic zones of the Canadian Prairies were analyzed using CuO oxidation and gas chromatography-mass spectrometry (GC-MS) to investigate the stage of lignin degradation. Parameters based on the CuO oxidation products were calculated for the soils and corresponding vegetation to determine the lignin sources and to monitor the lignin degradation. In addition to the widely used lignin monomer parameters, parameters resulting from lignin-derived phenolic dimers are used for the first time to assess lignin degradation in soils. The composition of lignin-derived phenols (S/V, C/V) in soil closely matches the composition observed in their respective source plants (grass, Aspen, Pine) reflecting the preservation of characteristic lignin patterns in soils. Degradation parameters based on lignin phenols and benzenes derived from tannins or other phenolic biomolecules indicate a progressive degradation from the vegetation to the soil horizons. In addition to commonly used lignin monomer indicators, parameters based on the lignin dimers are applied. Lignin degradation is found to be lowest in the Pine forest, intermediate in the grassland soils and highest in the Aspen-grassland transition soil. Degradation parameters based on non-lignin aromatic derivatives (3,5-dihydroxybenzoic acid, benzenepolycarboxylic acids) demonstrate a similar trend. The lignin from samples in the cooler climate (Black Chernozems) is observed to be more oxidized than in the soils from the warmer climate (Brown Chernozems) suggesting that abiotic processes may be in involved in the alteration of lignin and other phenolic biomolecules in soils. The results indicate that the comparative analysis of CuO oxidation products of soils and source vegetation is a valuable tool to assess the sources and degradation of lignin in soils.
Keywords: FOREST SOILS; GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS); GRASSLAND SOILS; LIGNIN BIOMARKERS; SOIL ORGANIC MATTER